Improving Shooting Ability in Football Games Through Leg Muscle Strength Training - Syahlidan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Gaming is a type of sport where two teams compete to win. However, not many leg muscle training activities are carried out in soccer games. For this reason, this research aims to prove the effectiveness of leg muscle training in improving shooting ability in soccer games. The research is experimental with a one-group-pretest and posttest design. The sampling technique was perposive sampling to obtain a research sample of 30 students from State Junior High School 1 Lokop. The research results showed that there was a significant increase in the average score of the posttest compared to the pretest. The increase occurred due to leg muscle strength training using the circuit method, namely the movement between posts. Thus, leg muscle strength training is effective in improving shooting ability in soccer games.